Penggunaan Teknologi Pada Manajemen Sumber Daya Manusia Di Dalam Era Digital Sekarang - Dian Sudiantini; Aura Naiwasha; Auranisa Izzati; Avrilia Ayunia W; Brilian Putri A; Cindy Rindiani (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
In the current era of digitalization and globalization, information and communication technology has become an integral part of human life. The use of technology which is growing rapidly has also affected almost all aspects of life, including in the world of work. Technology has made work easier, increased productivity, and opened up new opportunities for companies to grow faster. Information and communication technology has now become an important factor in changing the way companies operate. Companies that are successful in dealing with technological change and can utilize it effectively will have a competitive advantage in the market. Therefore, Human Resource Management has undergone many changes since the start of the digital era. The digital era has had a significant impact on the way companies recruit, train and motivate their employees. In the digital era, companies not only need to understand technology, but also need to understand how technology can assist in their human resource management